Syntactic Layer Analysis of the Poetry Of Az-har and Maz-har from Nizari Qohestani - S.Mahdi Rahimi; Fereshteh Golsorkhi; Mohammad Behnamfar; Akbar Shayan Seresht (مطالعات زبانی و بلاغی)
In this article, after a brief description of Nizari Qohestani and the poetry of Az-har and Maz-har, the theoretical discussions such as style, stylistics, and layer stylistics are defined. Then based on Cochran formula and statistical methods, benchmarks such as the sequence of sentence components, style and structure of sentences, the length of sentences, and the perspective, the semantic role of sentences and imperative language is analyzed. The results of this research show that although this opus is a poetry, but more than 60 percent of the sentences have standard and natural structures. The average length of sentences is 5.4 words, which indicates short, clear and explicit sentences. 80.58% of the sentences are simple and independent, the style of this work is discrete. 90.09% of sentences are declarative and nearly 90 percent are predicative and 73.1 percent of the sentences have an active tone.  Considering that this poetry is an epic Gemini and needs an active subject.